EMPOWERING PAWANG UTEUN (LOCAL FOREST HANDLERS) AS CUSTOMARY INSTITUTIONS TO COMBAT ILLEGAL LOGGING IN NORTH ACEH DISTRICT (UUM Journal of Legal Studies, 2026)
Illegal logging remains widespread in the protected, conservation, and production forests of North Aceh District, despite the government’s reliance on repressive enforcement measures. This persistence stems from limited personnel and the vast forest coverage, which undermine effective law enforcement. To address this issue, this qualitative study adopts an empirical legal approach to explore how empowering local forest custodians (pawang uteun) can enhance the prevention and prosecution of illegal logging. Primary data were collected through interviews and secondary data were gathered from literature and documentation. The findings reveal that while pawang uteun are recognized under Law No. 44/1999 on the Implementation of Aceh's Privileges, Law No. 11/2006 on the Government of Aceh, and Aceh Qanun No. 10/2008 on Customary Institutions, these provisions do not grant them sufficient authority to participate in law enforcement. This study recommends that the Aceh government promptly revise local regulations to formally integrate customary institutions, such as pawang uteun, into forest protection efforts. This study contributes to forest governance by proposing the Pawang Uteun Empowerment Model, which strengthens community-based participation in combating illegal logging in North Aceh.
Keywords: Empowerment; customary law; pawang uteun; illegal logging; North Aceh District